The Role of Fiscal Policy in Reducing Gender Income Inequality - Galvani, Selly; Nasrudin, Rusan (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2024)
Purpose This research aims to determine the role of fiscal policy in reducing gender income inequality in Indonesia. Design/methodology/approach This research used the microsimulation INDOMOD model, which is a static tax-benefit microsimulation model that has been underpinned by BPS Susenas 2019 data. Findings The estimation results show that the most appropriate fiscal policy to reduce gender income inequality are through PKH and BPNT. Meanwhile, income taxes for upper income levels have almost no effect, and for lower income levels, although it can reduce gender income inequality, it will increase income inequality. Research limitations/implications This research has several limitations which can be explored for further research. First, due to the limitations of the data, the gender term used refers to the gender of the head of household, so it does not describe the actual gender condition of the individual. Second, the income tax is calculated based on the income data available in the income block in the Susenas, so that the value does not reflect the actual condition of the income and income tax paid by taxpayers. Third, the microsimulation method is static, so it cannot be used to analyze the dynamic changes that occur at the individual level. Originality/value There are many studies on the relationship between fiscal policy and gender equality, but similar studies are still very limited in Indonesia. Moreover, the INDOMOD microsimulation model is rarely used in Indonesia, even though this method has been widely used in many countries.